THE USE OF CONTEXTUAL TEACHING AND LEARNING METHOD TO IMPROVE THE STUDENTS’ UNDERSTANDING ON THE USE OF RELATIVE CLAUSE - Badriyah Badriyah; Rinda Hardiyanti; Dian Saputra (Universitas Muhammadiyah Sorong, 2017)
Abstract This research was conducted to find out whether or not The Use of Contextual Teaching and Learning Method was Improve Students’ Understanding on The use of Relative Clause at Sorong Muhammadiyah University. The research method employed was quasi experimental groups. The population of this research was conducted at fifth semesters on English Education Department at Sorong Muhammadiyah University. The sample was chosen by applying stratified sampling technique. This research assigned two groups namely control and experimental groups. Each group consisted of 20 students.. Instrument of this research was test. The research gets the result that Contextual Teaching and Learning Method was effective to improve students’ understanding on the use of Relative Clause. The result of test showed that there was significant progress in students. The results of the research showed that mean score posttest of the experimental group was 84 and the control group was 80. It means that the result of the mean score posttest of experimental group is higher than control group. By using the degree of significance 5% or 0.05 in the t-table it was gotten 2.021. So that t-test value was more than of t-table value (H1: 5,31 > 2.021), So that alternative hypothesis is accepted, while Null hypothesis is rejected (Ho: 5,31 < 2.021). It can be proved that there was a significant on Contextual teaching and Learning method to improve students’ understanding on the use of relative clause. Key words: Relative Clause, Contextual Teaching and Learning.